What makes the application of peace journalism in Indo-Pak conflicts a Challenging task? - Muhammad Ashraf Wani; Bakht Rawan; Muhammad Sher Juni (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Building on the existing literature, this critical review of peace journalism scholarship — based on various research studies from 2002 to 2017— observed that application of peace journalism in reporting Pakistan-India relations, particularly conflicts, has become a challenging task due to various media tendencies. The prominent among these tendencies are the nationalistic, jingoistic and ethnocentric approaches in media coverage, wherein the media look into the issues from these particular lenses. The inclination of media to become party in conflicts, instead of adhering to the universal journalistic principles of impartiality and objectivity, led to biased coverage, and resultantly peace journalism was the victim. “Us versus Them” or “Our side and Other side” media inclinations are also taking the application of peace journalism away from the practice. While reliance on official sources for information and the structural constraints of news media, are the other factors that keep media away from reporting the conflicts from a peace perspective.